2008
DOI: 10.1097/olq.0b013e31815b0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Female Sex Workers With US Clients in Two Mexico-US Border Cities

Abstract: In these border cities, FSWs reporting US clients were more likely to have current STIs and to engage in higher-risk behaviors. Intensified binational prevention efforts involving both FSWs and their clients are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 19 publications
6
74
2
1
Order By: Relevance
“…Previous quantitative studies with female sex workers in Tijuana have highlighted the prevalence of risk behaviours among this population, including inconsistent condom use and injection drug use and the role of individual-based behaviour change models as a health promotion strategy (Patterson et al 2005(Patterson et al , 2008Strathdee et al 2008). The findings from the current study add to the results of these previous studies by highlighting the importance of incorporating how female sex workers define their health and body and identify the barriers and motivations for healthy lives.…”
Section: Discussionsupporting
confidence: 62%
“…Previous quantitative studies with female sex workers in Tijuana have highlighted the prevalence of risk behaviours among this population, including inconsistent condom use and injection drug use and the role of individual-based behaviour change models as a health promotion strategy (Patterson et al 2005(Patterson et al , 2008Strathdee et al 2008). The findings from the current study add to the results of these previous studies by highlighting the importance of incorporating how female sex workers define their health and body and identify the barriers and motivations for healthy lives.…”
Section: Discussionsupporting
confidence: 62%
“…3 Lastly, FSWs who inject drugs may be more willing to have unprotected sex for a higher payment to support their drug habit. 13,19,20 The context of sex work plays a role in FSWs' risk of HIV transmission. [21][22][23][24][25][26][27] In recent years, there has been an increasing acknowledgement of and interest in the role of social and structural factors in influencing risk behaviors and HIV/STI transmission.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Other STIs, which increase the risk for HIV acquisition and transmission, have also been repeatedly found to be more prevalent among FSWs as compared with other women. [12][13][14][15][16][17] Additionally, research has documented high rates of both injection and non-injection drug use among FSWs. 18 The synergistic relationship between drug use and transactional sex is bidirectional.…”
Section: Introductionmentioning
confidence: 99%
“…More than two-thirds of FSWs in Tijuana and Cd. Juarez reported being patronized by clients from the United States; these women were more likely to inject drugs, have syphilis, and report having unprotected sex for higher pay (61). In a study of 400 US and Mexican men who had paid for sex with FSWs in Tijuana, 50% reported having unprotected sex with FSWs within the past four months (48) that was associated with drug use during sex (21).…”
Section: Brief Skills-based Interventions To Increase Condom Use Amomentioning
confidence: 99%